Functional and radiological assessment of total ankle replacement with infinity prosthesis - Guerrero Forero, Álvaro Santiago; Rodríguez Ciodaro, Ricardo; Castillo Forero, Carlos; Caicedo Donoso, Claudia (Journal of the Foot & Ankle, 2021)
Objective: To present mid-term functional and radiological outcomes obtained with the use of Infinity prosthesis in Bogotá (Colombia). Methods: This cross-sectional observational study selected consecutive patients subjected to total ankle replacement with the fourth generation Infinity prosthesis (Wright Medical Technology). Results: Fifty-two patients with ankle arthrosis were followed for a mean period of 24 months, and the most frequently reported case of joint degeneration was trauma. Postoperative improvement was observed in perception of pain (visual analog scale increased from 8/10 to 2/10; p<0.0005), AOFAS functional scale (from 23 to 84.5; p < 0.0005), and range of motion (from 11° to 29°; p<0.0005). Similarly, radiological findings, implant positioning, and signs of loosening did not reveal implant failure. Conclusions: The use of fluoroscopically navigated prostheses allows us to achieve predictable outcomes, with satisfactory mid-term clinical and imaging results. Level of Evidence IV; Therapeutic Studies; Case Series.